Recovered memories of trauma as a special (or not so special) form of involuntary autobiographical memories - Dodier, Olivier; Barzykowski, Krystian; Souchay, Céline (Frontiers in Psychology, 2023)
Recovered memories of trauma are memories of traumatic events experienced generally during childhood, but of which the persons were unaware until they retrieved it. Legal decisions are sometimes based on such recovered memories, the validity of which is often questioned. Yet, people can recover genuine traumatic memories of childhood abuse. In this paper, we present and further discuss the idea that recovered traumatic memories can be interpreted in the context of the autobiographical memory framework. Specifically, we argue that recovered memories may be accessed after exposure to incidental cues that initiate unexpected spontaneous memory retrieval. Thus, we relate the recovered memory phenomenon to involuntary autobiographical memories and argue that it is an example of highly stressful, emotionally negative, and intense involuntary memories that were yet never recalled. This novel, evidence-based perspective leads us to reconsider the examination of the validity of eyewitness testimony as a continuum ranging from the least valid form (i.e., memories recovered in highly suggestive context facilitating its factitious reconstruction) to the most valid form (i.e., memories that were triggered by cues without any person’s voluntary engagement), and this in relation with how internal (e.g., age and internal cue) or external (e.g., suggestion in therapy, suggestion during investigative interview, and contextual cue) factors may influence memory retrieval. Finally, we propose several recommendations for experts that may be useful in assessing the validity of a testimony based on recovered memories.